ANALISIS KINERJA PADA BADAN KESBANGPOL & LINMAS (ANGGARAN BELANJA DAN REALISASINYA) DI KABUPATEN KUTAI BARAT - Suryanti, Ririn (EKONOMIA, 2012)
Regardless of the weaknesses and shortcomings that exist in it, the birth of Law. And No. 22. 25, among others, is the embodiment of the government's pergesean system, the centralized system to the decentralized system. Both the Act contains some explicit mission. First, create efficiency and effectiveness of resource management area. Second, improve the quality of public services and social welfare. Third, empower and create a space for people to participate in the development process. To realize this mission, the necessary changes to local government financial management system. The changes implemented by giving autonomy to regions based on the principle of decentralization in the form of autonomy, real and responsible.The purpose of this study was to determine whether the implementation of regional autonomy shows performance Performance Unit (SKPD) Kesbangpol & Community Protection Agency West Kutai district is likely to increase in 2011 compared to 2010.Performance analysis shows that the Regional Working Units (SKPD) Kesbangpol & Community Protection Agency West Kutai regency in 2011 tended to increase compared to 2010. Based on a comparative analysis of absolute data in 2011 Revenue and Expenditure can eventuated by 95.58% while in 2010 Revenue and Expenditure amounted to 94.89% eventuated.Based on the analysis, the authors provide some suggestions that regional work units (on education) Kesbangpol & Community Protection Agency and should be able to continue to maintain and improve the performance achieved so far, and future. And furthermore should further enhance coordination between each field in carrying out activities in accordance with the Budget Implementation Document (DPA) or Document Change Executive Budget (DPPA) that exist so as to achieve the targets set.